2016
DOI: 10.1159/000445046
|View full text |Cite
|
Sign up to set email alerts
|

Initial Research on Postoperative Management of Tetralogy of Fallot with Major Aortopulmonary Collaterals

Abstract: Objectives: Tetralogy of Fallot (TOF) with major aortopulmonary collaterals (MAPCA) is a well-known but always severe congenital heart disease. This study was designed to explore proper management after radical correction of TOF with MAPCA based on a hierarchical approach. Methods: The following data were collected from 39 patients planned to undergo radical correction of TOF: age, weight, number of aortopulmonary collaterals, total lumen diameter and collateral diameter-to-body weight ratio, transcatheter occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Also, hybrid surgery has been performed for patients with large lung disease and multiple or large feeding arteries or aneurysmal abnormal arteries (14-17). Patients with larger feeding arteries may be at high risk for incomplete embolism, which may require reoperation due to recanalization and symptom recurrence as described in our previous work (18)(19)(20)(21). In the present case, the patients feeding artery opening was 4 mm, and the possibility of incomplete embolization was low.…”
Section: Discussionsupporting
confidence: 61%
“…Also, hybrid surgery has been performed for patients with large lung disease and multiple or large feeding arteries or aneurysmal abnormal arteries (14-17). Patients with larger feeding arteries may be at high risk for incomplete embolism, which may require reoperation due to recanalization and symptom recurrence as described in our previous work (18)(19)(20)(21). In the present case, the patients feeding artery opening was 4 mm, and the possibility of incomplete embolization was low.…”
Section: Discussionsupporting
confidence: 61%
“…In our former study, we proposed to set collateral diameter-to-body weight ratio as the measure of whether further treatment of aortopulmonary collaterals is needed and provided preliminary ideas for the treatment of MAPCAs [11]. In the further study, we found that the collaterals are always multiple and different in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…The images and statistics data used to support the findings of this study are available from the corresponding author upon request. Part of those is from previously reported studies and datasets, which have been cited at relevant places within the text as Reference [11].…”
Section: Data Availabilitymentioning
confidence: 99%
“…Previous studies showed that the presence of enlarged APCs was associated with prolonged hospital stay [ 1 ] or ventilation [ 3 ]. However, the current literature has yet to correlate the quantitative amount of APCs with early postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Given that APCs appear to be very common in TOF, establishing cut-off point of APC density predicting unfavourable in-hospital outcome is warranted to guide the clinical practice. Some authors suggested that, based on their clinical observation, APC reduction should be performed in patients with an APC diameter-to-body weight ratio of >0.5 mm/kg [ 3 ] or diameter >2 mm [ 11 ]. However, the association between these criteria and postoperative outcome has not been validated.…”
Section: Discussionmentioning
confidence: 99%